Bromine-bridged Dy2 single-molecule magnet: magnetic anisotropy driven by cis/trans stereoisomers. Issue 97 (20th November 2019) - Li, Min; Wu, Haipeng; Xia, Zhengqiang; Montigaud, Vincent; Cador, Olivier; Le Guennic, Boris; Ke, Hongshan; Wang, Wenyuan; Xie, Gang; Chen, Sanping
Abstract : The peculiar cis / trans stereoisomers in a bromine-bridged Dy2 single-molecule magnet drive the orthogonal magnetic moments and tune the magnetic interactions, leading to a large energy barrier of 684 K. Abstract : We report the first bromine-bridged dinuclear [Dy(Cy3 PO)2 (μ-Br)(Br)2 ]2 ·2C7 H8 single-molecule magnet with an effective energy barrier of 684 K and magnetic hysteresis below 3 K. The asymmetric Dy III centres present two unique stereoisomeric octahedral coordination environments depending on the cis / trans disposition of the Cy3 PO ligands, leading to the orthogonality of the easy magnetic axes that annihilates the dipolar interactions.